MASALAH KEMISKINAN DAN STRATEGI PEMBERDAYAAN MASYARAKAT JAKARTA - Gumilar Rusliwa Somantri (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2006)
Poverty is one of the problems which often shadowing the growth of city. Integration the city toward global economic system, has stimulated economic growth and prosperity for Urban citizen.